The Effect of Using Master Rheobuild 6 Towards Compressive Strength and Porosity of Concrete - Pribadi , Juli Ardita; Muhammad Gala Garcya,; Dedi Enda, (Journal of Structural Monitoring and Built Environment, 2022)
Bengkalis Regency is an island where almost all of its land is peat soil. Peat is a soil layer rich in organic matter. The organic matter that makes up the soil is formed from the remains of dead and weathered plants. This area is also located in the middle of the ocean and the absence of rivers and mountains in the area so construction materials were imported from Tanjung Balai Karimun. Coarse and fine aggregates in the area are exposed to high salt content also no fresh water meets the basic specifications of concrete design. This research uses additives to improve the quality of concrete. This study used cylindrical concrete measuring 105 x 210 mm and as many as 27 samples for testing compressive strength and porosity with a treatment period of 14 and 28 days. based on the results of compressive strength, the addition of 1.5% additive by weight of cement resulted in compressive strength of up to 35.39 MPa compared to normal concrete which only reached 32.71 MPa. Meanwhile, for the porosity test with the addition of 1.5% additive, the porosity value was 4.75% compared to normal concrete, which was 10.45%. This study highly recommends the use of this additive in concrete work so that based on the tests carried out, the quality of the concrete is high and the porosity is relatively small so it is not easy for water to enter the concrete which has an impact on the performance of the concrete material itself.